THE ANALYSIS OF SECOND LANGUAGE ACQUISITION IN CHILDREN VS ADULTS - Wibowo, Amiruddin Hadi; Agustina, Eliasanti; Wardhani, Norita Prasetya (Journal of Education and Research, 2024)
This article aims to provide a comprehensive analysis of the interaction between children and adults when learning a second or foreign language, to offer a more coherent and academic response to the question of whether children outperform adults in second language acquisition. The process of learning a second language can occur naturally, in formal instructional settings, or through social interactions. Several internal factors, such as the role of the first language, student motivation, and attitudes, play a crucial role in determining the proficiency level of second language learners. The findings of this study lend support to the notion that the aging process is correlated with a decline in the ability of pupils to recall language information. However, it is important to emphasize that successful second language acquisition is not solely determined by age, but rather hinges on the individual's intrinsic motivation to engage in meaningful communication and interaction with others through the medium of a second or foreign language.